RENTABILIDADE DAS EXPORTAÇÕES BRASILEIRAS DE MADEIRA TROPICAL - Angelo, Humberto; Hosokawa, Roberto Tuyoshi; Berger, Ricardo; Castro, Luis Hernan Rodríguez (Floresta, 2003)
Este trabalho estima e analisa as exportações de madeiras serradas tropicais no que diz respeito à rentabilidade. O comportamento dessas exportações foi estimado a partir dos indicadores de taxa real de câmbio e de rentabilidade para melhor explicar o desempenho das exportações das madeiras tropicais brasileiras, para o período de 1972 a 1994. A rentabilidade das exportações foi crescente até meados da década de 80, a partir de então, uma queda acentuada foi verificada. PROFITABILITY OF BRAZILIAN TROPICAL SAWNWOOD EXPORTS Abstract This work analyses the Brazilian tropical sawn wood exports, taking into consideration its performance and profitability. Indexes of real exchange rate and export profitability were estimated for the period 1972-94 in order to better explain the Brazilian sawn wood competitiveness in the international market. It was found that the profitability of the exports increased until the middle of the 80’s. Since then, an accentuated decline was verified.